Energetic Cost and Kinematics of Pushing a Stroller on Flat and Uphill Terrain - Sandbakk, Øyvind; Perl, Rilana; Holmberg, Hans-Christer; Steiner, Thomas (Frontiers in Physiology, 2020)
During early parenthood, walking and/or running while pushing a stroller is a common form of endurance exercise among both recreationally active individuals and athletes. Here, we investigate how pushing a stroller influences the energetic cost, gross efficiency and kinematic behaviour of well-trained men and women while walking or running on flat and uphill incline. Eight men and nine women, all recreationally active, performed three 5-min submaximal tests of walking or running during four different testing sessions, in randomized order: with and without pushing a 24.3-kg stroller on a flat (1%; 6, 8/9 and 11/12 km/h for women/men) and uphill (10%; 5, 6.5/7.5 and 7.5/8.5 km/h for women/men) incline. Respiratory parameters, heart rate, blood lactate concentration and rating of perceived exertion (RPE) were determined and video-based kinematic analysis was performed in connection with all these tests. Except while walking on the flat incline, pushing a stroller increased the energetic cost of walking/running under all conditions (all p<0.05). This was associated with shorter and more rapid strides on both inclines (all p<0.05); however, gross efficiency was higher when pushing the stroller (p<0.05). The increase in energetic cost of pushing the stroller was approximately three-fold higher uphill than on the flat incline, and women were influenced more than men when running uphill at the highest speed (all p<0.05). Here, we provide novel insights on the energetic cost and kinematic behaviour of pushing a stroller while walking or running on flat and uphill inclines. The energetic cost of pushing a stroller was clearly higher than for unloaded exercise, coincided by shorter and more rapid strides, and especially pronounced on uphill terrain where also women were more influenced than men.